All adults here eaudiobook A novel. - Straub, Emma (Penguin Audio, 2020)
AN INSTANT NEW YORK TIMES BESTSELLER A TODAY SHOW #ReadWithJenna BOOK CLUB PICK! "In a time when all we want is hope, it’s a beautiful book to reach for." -Jenna Bush Hager "Brimming with kindness, forgiveness, humor and love and yet (magically) also a page turner that held me captive until it was finished. This is Emma Straub's absolute best and the world will love it. I love it." — Ann Patchett “An immensely charming and warmhearted book. It’s a vacation for the soul.”—Vox A warm, funny, and keenly perceptive novel about the life cycle of one family—as the kids become parents, grandchildren become teenagers, and a matriarch confronts the legacy of her mistakes. From the New York Times bestselling author of Modern Lovers and The Vacationers , and the forthcoming novel This Time Tomorrow . When Astrid Strick witnesses a school bus accident in the center of town, it jostles loose a repressed memory from her young parenting days decades earlier. Suddenly, Astrid realizes she was not quite the parent she thought she'd been to her three, now-grown children. But to what consequence? Astrid's youngest son is drifting and unfocused, making parenting mistakes of his own. Her daughter is pregnant yet struggling to give up her own adolescence. And her eldest seems to measure his adult life according to standards no one else shares. But who gets to decide, so many years later, which long-ago lapses were the ones that mattered? Who decides which apologies really count? It might be that only Astrid's thirteen-year-old granddaughter and her new friend really understand the courage it takes to tell the truth to the people you love the most. In All Adults Here , Emma Straub's unique alchemy of wisdom, humor, and insight come together in a deeply satisfying story about adult siblings, aging parents, high school boyfriends, middle school mean girls, the lifelong effects of birth order, and all the other things that follow us into adulthood, whether we like them to or not.